2023
DOI: 10.1002/anie.202305775
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry‐Amended Barbier Reaction as an Expedient Alternative to Grignard Synthesis**

Abstract: Organomagnesium halides (Grignard reagents) are essential carbanionic building blocks widely used in carbon‐carbon and carbon‐heteroatom bond‐forming reactions with various electrophiles. In the Barbier variant of the Grignard synthesis, the generation of air‐ and moisture‐sensitive Grignard reagents occurs concurrently with their reaction with an electrophile. Although operationally simpler, the classic Barbier approach suffers from low yields due to multiple side reactions, thereby limiting the scope of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In 2021, the groups of Ito [12] and Blom [13] reported their independent works on the mechanochemical Grignard reactions involving various electrophiles (especially poorly soluble aryl halides and CO 2 gaseous) and nickel‐catalyzed Kumada—Tamao–Corriu coupling reactions based on the ‘one‐jar’ prepared organo‐magnesium reagents. Very recently, Aav and Kananovich developed a novel mechanochemical Mg‐mediated Barbier reaction, which provides an expedient alternative to conventional solution reactions [14] . Notably, the ethereal additives (liquid‐assisted grinding solvent), especially tetrahydrofuran, play critical roles in determining the reactivity of these transformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, the groups of Ito [12] and Blom [13] reported their independent works on the mechanochemical Grignard reactions involving various electrophiles (especially poorly soluble aryl halides and CO 2 gaseous) and nickel‐catalyzed Kumada—Tamao–Corriu coupling reactions based on the ‘one‐jar’ prepared organo‐magnesium reagents. Very recently, Aav and Kananovich developed a novel mechanochemical Mg‐mediated Barbier reaction, which provides an expedient alternative to conventional solution reactions [14] . Notably, the ethereal additives (liquid‐assisted grinding solvent), especially tetrahydrofuran, play critical roles in determining the reactivity of these transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Aav and Kananovich developed a novel mechanochemical Mgmediated Barbier reaction, which provides an expedient alternative to conventional solution reactions. [14] Notably, the ethereal additives (liquid-assisted grinding solvent), especially tetrahydrofuran, play critical roles in determining the reactivity of these transformations. Besides the preparation of organomagnesium reagents, two cases from our research group indicated that mechanochemically activated magnesium metal can also act as a key active mediator for the generation of radicals and endow regiocontrol of the CÀ H alkylation of azaarenes.…”
Section: Introductionmentioning
confidence: 99%
“…This method is distinguished by its bene ts including abbreviated reaction times, the use of insoluble starting materials, minimal solvent/reagent consumption, and enhanced reaction activity and selectivity. [34][35][36][37][38][39][40] Recently, research teams led by Harrow eld, 41 Hanusa, 42 Ito, 43 Bolm, 44 Kananovich, 45 Wei, 46 and Yu [47][48] have exploited ballmilling conditions to activate C-X (X= I, Br, Cl) bonds using metallic magnesium, facilitating the synthesis of Grignard reagents that proved effective in organic synthesis. Despite these advancements in generating Grignard reagents under mechanochemical conditions with zero-valent magnesium, the mechanochemical activation of aryl uorides remains underexplored due to the inertness of the C-F bond, which displays limited e ciency.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Mechanochemistry is already widely used in many areas of chemistry 3 but has only recently started to make an impact in main group synthesis. [4][5][6][7][8][9][10][11] Some examples of note include Kubota, Ito and co-workers 2021 report that Grignard reagents can be synthesised mechanochemically in high yields (Fig. 1, I).…”
mentioning
confidence: 99%